Sequência didática em perspectiva dialógica para ensino de ecologia - Bitarães, Vitória da Silva (Universidade Federal de São Carlos, 2022)
In biology teaching, and specifically in ecology teaching, the contents are fragmented. In addition, it uses teaching and learning approaches, developed in and for industrial societies, as is the case of significant learning, but in contemporary societies are information and knowledge, enabling communicative and dialogic interactions, but also increasing risks. Thus, it is necessary the use of teaching and learning perspectives that respond to these societies and at the same time enable the transformation of unequal conditions. The present work aimed to propose and analyze the proposal of a didactic sequence in the teaching of ecology from the Dialogical Learning and methodologically structured in the Three Pedagogical Moments. Both references are due to the dialogic action present in their own foundations. Moreover, it had as thematic approach, the disappearance of bees, enabling studies about the Ecological Balance. Finally, it is concluded that it is possible to study the contents in the school from the contemporary, but it is necessary the application of this didactic sequence to analyze the real effects on the learning of the students.
Didatic sequence in dialogical perspective for ecology teaching
Keywords: Equilíbrio ecológico; Sociedade da informação; Ensino de biologia; Biology teaching; Information society; Ecological balance; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO